The Influence Of Religiosity On Islamic Consumption Behavior Patterns At Mahasantri Ma’had Al-Jami’ah UINFAS Bengkulu - Neneng Aspriyanti; Asnaini Asnaini; Herlina Yustati (UNIVED Press, 2024)
The aim of this research is to determine whether or not there is an influence of religiosity on Islamic consumption behavior patterns at Mahasantri Ma’had Al-Jami’ah UINFAS Bengkulu. This type of research is quantitative research with a regressional approach. The data collection techniques for this research are questionnaires and documentation. The data validity technique is testing the validity and reliability of the data. The data analysis techniques are normality test, homogeneity test, regression linearity test, data hypothesis test (t test), simple regression test, and coefficient of determination test (R2). The results of this research are that there is a significant influence between religiosity on Islamic consumption behavior patterns at Mahasantri Ma’had Al-Jami’ah UINFAS Bengkulu. This is known from the results of the hypothesis test which was carried out using a simple regression test. The calculation result was that the value b = 0,348 which means that every time variable X (religiosity) increases by one, the average of variable Y (Islamic consumption behavior) increases by 0,348. Likewise, the t count value obtained is 3,845 and the t table value is 1,668 so the t count > t table or 3,845 > 1,668 so it can be concluded that Ha is accepted and H0 is rejected, which means that there is an influence of religiosity on Islamic consumption behavior patterns at Mahasantri Ma’had Al-Jami’ah UINFAS Bengkulu. Meanwhile, the calculation result of R Square (R2) is 0,625 which shows that there is an influence of religiosity on Islamic consumption behavior of 62,5%, while 37,5% is where Islamic consumption behavior is influenced by other variables not examined in this research.